THE SUITABILITY OF TEXTBOOK FOR THE FIRST YEAR OF JUNIOR HIGH SCHOOL WITH THE COMPETENCY-BASED CURRICULUM - SETYONINGRUM , MARIA DWI (2006)
In this research, the writer describes the suitability of textbook for the first year of Junior High school with the Competency-based Curriculum. This research has two objectives; to describe whether the theme and structure skills are suitable with the Competency-based Curriculum. The type of this research is qualitative research in which the object of this research is the theme and structure skills contained in three English textbooks used by first students of Junior High School. In line with the objective the research-the writer used a descriptive method. In collecting the data, the writer used documentation analysis as the instrument. The data were analyzed by: 1) Finding out the kinds of themes and structure skill available on the textbook, 2) Classifying them, 3) Analyzing them, 4) Counting and adding them, 5) Giving percentage from the total number, 6) Judging whether the data are appropriate with indicators in Competency-based Curriculum or not, and 7) Making conclusion and suggestions. The result of the research shows that the first book entitled The Bridge English Competence has 100% for themes and 75% for structure skills. So the compatibility of this textbook is good. It means that the textbook is compatible with the English syllabus of Competency-based Curriculum. The second English textbook Smart Step has score 100% for themes and 87,5% for structure skills. So the compatibility of this book is very good. It means that the textbook is very compatible with the English syllabus of Competency-based Curriculum. The last textbook English for Junior High School Textbook has score 100% for themes and 68,75% for structure skill, so the compatibility of this book is fairly good. It means that the textbook is fairly compatible with the English syllabus of Competency-based Curriculum. Finally, the writer concludes that the three textbooks can be used by the first year students of Junior High School although the first and the third English textbook still need to be improved and revised.